The global manager's guide to cultural literacy - Grosse, Christine Uber (Cambridge Scholars Publishing, 2019)
Global managers need to communicate and connect with many different cultures. The new language of business is cultural literacy, which encompasses basic knowledge of business language, culture and the local economy.This book provides a general overview and specific examples of cultural literacy. It will provide managers with a basic understanding of the business language, culture and economy of seven countries in the G-20, including Brazil, Mexico and the US in the Americas, China and South Korea in Asia, and France and Germany in Europe.For global managers, knowing even the basics about a cou.